Narasin Supplementation Enhances Growth Performance in Grazing Cattle - Daniel M. Polizel; Rodrigo S. Marques; Arnaldo C. Limede; Fernando A. A. Cidrini; José Renato S. Gonçalves; Pedro H. V. Carvalho; Alexandre V. Pires (Animals, 2025)
Three experiments were conducted to evaluate the effects of narasin inclusion on the growth performance of grazing beef cattle under similar forage availability and quality. All three experiments were arranged in a randomized complete block design according to the initial BW. Exp 1: 200 Nellore calves (initial BW = 177 ± 15 kg) were randomly allocated in three treatments for 84 d during the rainy season: (1) CONT: mineral supplement; (2) 1400 N: 1400 mg of narasin/kg of supplement; and (3) 2100 N: 2100 mg of narasin/kg of supplement. Narasin inclusion increased (p ≤ 0.01) ADG by 0.077 kg/d and final BW by 6.7 kg, with no differences (p ≥ 0.50) between narasin doses. Exp 2: 240 Nellore calves (initial BW = 195 ± 19 kg) were allocated to CONT or N1400 for 112 d during the rainy season. Narasin inclusion increased (p ≤ 0.01) ADG by 0.082 kg/d and final BW by 9.1 kg. Exp 3: 150 Nellore yearlings (initial BW = 332 ± 22 kg) were allocated for 112 d during the dry season: (1) PROT: protein supplement and (2) PROT250: inclusion of 250 mg of narasin/kg of supplement. Narasin inclusion increased (p ≤ 0.04) ADG by 0.048 kg and final BW by 5.3 kg. For all experiments, narasin inclusion did not impact (p ≥ 0.25) supplement intake. Hence, inclusion of narasin in mineral and protein supplements consistently enhances growth performance of grazing beef cattle across different seasons and production stages, without impacting supplement intake, providing an effective nutritional strategy to enhance productivity on tropical pastures.